The Effect of Powtoon-Based Audiovisual Media on Indonesian Language Learning Outcomes - Fitriyani, Wiwid; Solihati , Nani (MIMBAR PGSD Undiksha, 2022)
The selection of inappropriate teaching tools, lack of innovation, and the lack of technological media provided by the teacher causes students to have difficulty learning Indonesian. This study aims to analyze the effect of powtoon-based audiovisual media. This type of research is quantitative. The quantitative approach with the research method used in this study is the Nonequivalent Post-test Only Control Group Design with the sample used for experimentation and as a control group and taken randomly from a specific population. The study's target population was 60 students consisting of 30 students from class VA (Experimental) as the saturated sample and 30 students from class VB (Control). The methods used to collect data are instruments and tests. The techniques used to analyze the data are qualitative descriptive analysis, quantitative analysis, and inferential statistics. The result of this research is that there is an effect of Powtoon-Based Audiovisual learning media on the Indonesian language learning outcomes of fifth-grade elementary school students. It was concluded that Powtoon-Based Audiovisual learning media could improve fifth-grade elementary school students' Indonesian language learning outcomes.